Innovative Strategies in Poverty Alleviation Based on Islamic Economic Principles - Khoirul Fathoni (Journal of Economics and Social Sciences (JESS), 2024)
This study aims to analyze innovative strategies in poverty alleviation based on Islamic economic principles through the Systematic Literature Review (SLR) approach. This study examined 21 Scopus indexed articles relevant to the theme of Islamic social finance and poverty alleviation. The results of the study show that the main instruments in Islamic economics, such as zakat, waqf, and sharia microfinance, have a significant role in wealth redistribution, community economic empowerment, and social inequality reduction. In addition, the concept of Islamic social business and solidarity economy also strengthens efforts to alleviate poverty in a sustainable manner. However, there are various challenges in its implementation, including limitations in the management and distribution of funds, low public literacy, and integration obstacles with the modern financial system. This study emphasizes that optimizing poverty alleviation based on Islamic economics requires a comprehensive, collaborative, and adaptive policy support. These findings make a theoretical and practical contribution to the development of more inclusive and sustainable poverty alleviation policies and programs.